An Intelligent Path Evaluation Algorithm for Congestion Control in Wireless Sensor Networks - Dr. Sukhkirandeep Kaur, Makul Mahajan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Wireless Sensor Networks (WSNs), congestion occurs when the traffic load on the node reaches obvious network channel power and is considered as a prominent problem. So it is highly essential to identify, prevent and fix congestion when taking into account the network’s restricted re- sources. If congestion in the network is not managed correctly, it can lead to significant loss of QoS parameters, such as decreasing network throughput, increasing energy usage, and decreasing the distribution ratio of packets at the destination or sink node. In this article, we have formulated an algorithm to manage congestion using a modified ant colony algorithm that considers the residual energy, buffer occupancy and bandwidth of the neighbour node for selecting the best node to route the traffic that needs strict QoS requirements. For routing the traffic, there may be a variety of neighbour nodes exists in the network ,and if congestion occurs at any selected neighbour node the algorithm will rework to check the quality of rest of the neighbor nodes by calculating a path preference probability metric. The neighbour node with maximum path preference probability will be selected for routing the data packets belonging to real-time traffic that have stringent QoS. The proposed algorithm was simulated and tested using NS 2.33 and it was found that as opposed to the standard AntSense algorithm, the proposed algorithm is capable of achieving lower average energy consumption and packet loss ratio respectively with higher throughput.